2012
DOI: 10.1590/s0100-204x2012000800019
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de bezerros aleitados com soro de queijo em associação ao colostro

Abstract: Resumo -O objetivo deste trabalho foi avaliar o desempenho de bezerros mestiços, aleitados com soro de queijo em associação ao colostro. Foram utilizados 24 bezerros Holandês x Zebu, distribuídos em delineamento inteiramente casualizado, com três tratamentos e oito repetições. Os tratamentos consistiram de: leite integral, 50% de leite integral + 50% de soro de queijo, e 30% de colostro + 70% de soro de queijo. O desenvolvimento dos bezerros foi avaliado até os 60 dias de idade, por meio de pesagens semanais e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
3
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 5 publications
1
7
3
8
Order By: Relevance
“…As expected, increased consumption over time was seen across all treatments. This agreed with the results found by Lima et al (2012) and Eckert et al (2015), who report that feed intake in the first weeks of life is small, since the calf can meet its nutritional requirements with whole milk; increasing solid food consumption increases when animals reach approximately 4 weeks of age. The regression equations that best represented the intake variables were: Y = -79.14 + 114.54X (R 2 = 0.93) for concentrate intake; Y = 34.68 + 13.69X (R 2 = 0.97) for hay consumption; and Y = 378.57 + 128.24X (R 2 = 0.94) for total dry matter intake, where Y represents the evaluated variable and X the experimental week.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…As expected, increased consumption over time was seen across all treatments. This agreed with the results found by Lima et al (2012) and Eckert et al (2015), who report that feed intake in the first weeks of life is small, since the calf can meet its nutritional requirements with whole milk; increasing solid food consumption increases when animals reach approximately 4 weeks of age. The regression equations that best represented the intake variables were: Y = -79.14 + 114.54X (R 2 = 0.93) for concentrate intake; Y = 34.68 + 13.69X (R 2 = 0.97) for hay consumption; and Y = 378.57 + 128.24X (R 2 = 0.94) for total dry matter intake, where Y represents the evaluated variable and X the experimental week.…”
Section: Resultssupporting
confidence: 92%
“…Both groups presented similar body development across the treatments. Lima et al (2012) also observed no significant differences in the dry matter intake of calves receiving whey in the liquid diet.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Porcentagem de soro ofertado na dieta 0 10 20 nutricional, é considerado uma alternativa viável na alimentação de bezerros como substituto do leite e, portanto, fator importante na diminuição do custo de cria desses animais (FONTES et al, 2006;LIMA et al, 2012). A inclusão de 10% de soro do leite na dieta dos bezerros experimentais proporcionou maior consumo de concentrado (p<0,05), o que poderia antecipar o desaleitamento.…”
Section: Parâmetros Avaliadosunclassified